A transformerless single-phase multilevel converter for grid-tie renewable energy systems. (May 2020) - Gunsal, Izgun; Stone, David A.; Foster, Martin P.
Abstract: A multilevel converter produces a high quality output voltage waveform therefore requires less filtering in grid-tie systems. Cascaded H-bridge converter is a favourable topology for a hybrid renewable and storage system due to isolated DC source requirement. This converter is designed to interface a hybrid photovoltaic and battery system to the utility grid, making DC sources more accessible. In this study, a nine-level cascaded H-bridge converter is presented. A closed loop controller implemented in synchronous rotating frame is used to control active and reactive power independently. The control strategy is implemented in a simulation environment and then validated with experimental results. The generated output current waveforms are analysed when operated with various sinusoidal pulse width modulation techniques such as phase disposition pulse width modulation. It is found that the converter has a low total harmonic distortion that conforms to IEEE 1547 standard.